Analisis Pengaruh Lingkungan Kerja, Kedisiplinan Pegawai, dan Kualitas Pelayanan terhadap Kepuasan Masyarakat pada Kantor Kecamatan Pengkadan Kabupaten Kapuas Hulu - Mirawati Mirawati; Arie Wibowo Khurniawan; Ake Wihadanto (Dinasti Research, 2024)
This study aims to analyze the influence of the Work Environment, Employee Discipline, and Service Quality on Public Satisfaction at the Pengkadan District Office, Kapuas Hulu Regency. This research uses a causal quantitative method and descriptive statistical analysis. Data were collected through questionnaires with a sample of 100 respondents selected randomly using convenience sampling. The sample was taken from individuals who had received services during February-March 2024, with a total population of 127 people. The data obtained were analyzed descriptively using the top two boxes approach and Partial Least Square-Structural Equation Modelling (PLS-SEM). The results showed that the Work Environment has a positive and significant effect on Employee Discipline and Service Quality, but no significant direct effect on Public Satisfaction. Employee Discipline also has a positive and significant effect on Service Quality, but no direct significant effect on Public Satisfaction. Service Quality itself has a positive and significant effect on Public Satisfaction. Indirectly, the Work Environment affects Public Satisfaction through Service Quality, and Employee Discipline also affects Public Satisfaction through Service Quality. However, no indirect effect of the Work Environment on Public Satisfaction through Employee Discipline was found.